Práticas e Apropriações na Construção do Urbano na Cidade de Aracaju/SE - Santos, Waldefrankly Rolim de Almeida (2007)
This study aims to insert the history of Aracaju city into an environmental history, whose questions reside to find the moments in which some premises and practices bad reintegrated were reforced in their foundation process, they have been remaining in the contemporary practices about their urban environment. Such worries at the present time join themselves, into the worries during the environmental crisis contemporary and the cities participation in this context. Like this, this work intends to contribute to the nature understanding of the relation man environment in their mechanisms of practices and appropriations into an environmental perspective, our objective is to describe and to analyze how evolved the urban legislation of Aracaju city in its environment perspective, among the decades from 1855 to 1920. In the same way, to understand how processed the management of Aracaju city in its initial years in the articulation of urban question with its development. Thereby, we search to understand several appropriations realized by competent discourse produced by intellectuals who themselves dedicated to the city and we crossed it into the legislation made to normalization and regulation of the urban legislation concurred to permanencies in the integration of urban question with its development. In this case, we understood that state actions were straight connected with the executing and elaborating of legal particularities that has permitted since the city origin, the rising of a tradition that has been prolonging itself in its history: The tradition of put land and destroy dunes to the promotion, struturaction and direct and indirect valorization of some specific areas of the city and the formation of an unstructured periphery with high occupation density. For better research operacionalization we applied to the urban legislation aracajuana the technique of the content analyze the urban Aracaju legislation and the usage concept definite by Michel de Certeau (1994) and applied to the city s users.